Persepsi Masyarakat terhadap Kegiatan Pasar Malam pada Akses Jalan Umum di Desa Bukit Pariaman, Kecamatan Tenggarong Seberang, Kabupaten Kutai Kartanetagara - Amalia Ayu Febrianti; Moh. Bahzar; Jawatir Pardosi; Wingkolatin Wingkolatin; Novita Novita; Suryaningsi Suryaningsi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to find out the public's perception of night market activities and the impact they have on road access in Bukit Pariaman Village, Tenggarong Seberang District, Kutai Kartanegara Regency.The type of data analysis carried out was using a qualitative descriptive analysis method. This research was carried out through interviews, field observations and document analysis. The research results show that the night market in Bukit Pariaman Village, which has been operating since 1995 and is held every Wednesday night, is an important economic and social center. However, limited parking space causes traffic jams that disrupt community activities. Inadequate infrastructure has also disrupted sales activities and reduced income since the Covid-19 pandemic. Parking money is channeled to the village treasury, but there has been no concrete solution from the market management and village government. This creates a feeling of discomfort felt by the community. Therefore, better management is needed, including providing parking lots, improving infrastructure and fair regulations. The community hopes that the village government will immediately provide a solution to reduce congestion and increase comfort. The research results recommend providing adequate parking, infrastructure improvements, more effective traffic management, transparency in financial management, and collaboration with the community to improve night market management in Bukit Pariaman Village.